Quantification of economic uncertainty for synthetic natural gas production in a H2O permeable membrane reactor as simultaneous power-to-gas and CO2 utilization technologies. (1st September 2019) - Lee, Boreum; Lee, Hyunjun; Kim, Sehwa; Cho, Hyun-Seok; Cho, Won-Chul; Jeon, Byong-Hun; Kim, Chang-Hee; Lim, Hankwon
Abstract: Economic uncertainty analysis of employing a membrane reactor (MR) equipped with H2 O separation membranes for a synthetic natural gas (SNG) production as simultaneous power-to-gas and CO2 utilization technologies was carried out. Based on previously reported reaction kinetics, process simulation models were created for a conventional packed-bed reactor (PBR) and an MR. Deterministic economic analysis showed the unit SNG production cost of 1.67 kgSNG −1 in an MR compared to 1.82 kgSNG −1 in a PBR for a SNG production capacity of 1000 kg d −1, showing about 8% cost reductions in the MR. From sensitivity analysis, raw material and labor were identified as the key economic factors to affect a unit SNG production cost for all cases studied. Stochastic economic analysis using a Monte-Carlo simulation method provided better insights for economic-uncertainty associated with premature technology like a SNG production in an MR using H2 O separation membranes by presenting a wide range of SNG production costs and their probability. Highlights: A H2 O permeable membrane reactor (MR) was proposed to improve SNG yield. Deterministic and stochastic economic analysis for SNG production were performed. For industrial-scale plant, the MR showed about 8% cost saving of a unit SNG cost. Uncertainty analysis presented a wide range of a unit cost from 1.01 to 2.28 kg −1 .